Tatwiru Mawadi Ta’limi Kitabi LKS fi an-Nahwi Bikitabi Kayfa Haluk bi an-Nahwi? Litalamidi al Fasli al-‘Asyir fi al-Fasli ad-Dirosi al-Awal bi al-Madrosah Ast-Tsanawiyah Al-Islamiyah YATPI Godong - Nur Sahid; Hasan, Moh. Abdul Kholiq; Nashirudin, Muh. (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
Abstract In fact, what happened at MA YATPI Godong was based on observations, many students still had difficulties in learning Arabic, especially in nahwu material, this is indicated by the number of students who took part in the Daily Assessment (PH) which was carried out at the end of one Basic Competence (KD) or some KD from each semester are still around 21-30% of students whose scores reach or above Minimum Completeness (KKM) while the rest still have difficulty answering the questions that have been provided, especially questions related to qoidah nahwu. This phenomenon is basically influenced by many factors, namely: 1) the learning process is not going well and not smoothly due to the lack of appropriate and adequate learning resources; 2) the teaching materials used are not relevant to the abilities and conditions of the students 3) the teaching materials do not meet content standards and curriculum standards; in the end the teacher is